THE EFFECT OF INTENSIVE ENGLISH CLASS ON STUDENTS’ LANGUAGE SKILL - Hafizhatu Nadia (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2018)
It is important for the students to enhance their language skill for the sake of academic purposes considering that most of their classroom materials are in English. To fully comprehending the material given to them, the students are required to use their reading and writing skills. Intensive English class (IEC) is conducted to facilitate the students’ needs for enhancing their language skills. This extracurricular activity which accommodates and prepares the students is held by Language Development and Service Centers at University of Muhammadiyah Banjarmasin. This paper is aimed to reveal the significance of IEC on enhancing students’ language skills. In order to fulfill this objective, the researchers apply pre-experimental research design. The researchers take 22 participants of the IEC as the object of the study and the data of this study is taken from questionnaire and students’ test result. The result of this study then expected to give a statistical data support for formulating a good Intensive English program.